System and method of using an atomic data buffer to bypass a memory location - Koker Altug; S Jayakrishna P; K Pattabhiraman (2016)
Methods and systems may provide for receiving a request to perform an atomic operation and adding the atomic operation to an execution pipeline of an arithmetic logic unit (ALU) for one or more pending atomic operations if the one or more pending atomic operations are associated with a memory location identified in the request. Additionally, at least a portion of the execution pipeline may bypass the memory location. In one example, adding the atomic operation to the execution pipeline includes populating a linked list with a modification associated with the atomic operation, wherein the linked list is dedicated to the memory location.